THE IMPACT OF TOTAL QUALITY MANAGEMENT ON SERVICE QUALITY, CUSTOMER ENGAGEMENT, AND CUSTOMER LOYALTY IN BANKING - Rosa Harimurti; Tatik Suryani (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2019)
The purpose of the research is to examine the impact of Total Quality Management (TQM) implementation on Service Quality, the effect of Service Quality on Customer Engagement and Customer Loyalty in banking industry. The other objective of the research also to examine the effect of Customer Engagement on Customer Loyalty. This research was conducted in East Java Province which involved 209 State Owned Enterprises (SOE) bank customer’s as respondents. All variables are measured by Likert scale from bank customer perspectives. By Partial Least Square SEM analysis, the research found that TQM practices has positive effect on Service Quality, Service Quality has positive effect on Customer Engagement and Customer Loyalty and Customer engagement has positive effect on Customer Loyalty. The implication of this research is that SOE banks should implement TQM well so that it has a positive impact on service quality.